Design of efficient graphene plasmonic coupling circuits for THz applications. Issue 3 (16th April 2020) - Amanatiadis, Stamatis A.; Zygiridis, Theodoros; Kantartzis, Nikolaos V.
Abstract : Purpose: The coupling characteristics between adjacent circuits are crucial for their efficient design in terms of electromagnetic compatibility features. Specifically, either the wireless power transfer can be enhanced or the interference can be limited. This paper aims to the extraction of the coupling characteristics of surface plasmon polariton waves propagating onto graphene layers to facilitate the telecommunication system design for advanced THz applications. Design/methodology/approach: The surface conductivity of graphene is described at the far-infrared spectrum and modelled accurately by means of a properly modified finite-difference time-domain) scheme. Then, a series of numerical simulations for different coupling setups is conducted to extract an accurate generalised parametric coupling model that is dependent explicitly on the fundamental propagation features of graphene. Findings: The coupling coefficients of two basic waveguiding setups are examined thoroughly. The initial one includes two parallel graphene layers of infinite dimensions, and it is observed that the coupling is influenced via the ratio between their distances to the confinement of the surface wave. The second scenario is composed of graphene microstrips that are parallel to their small edge, namely, microstrip width. The extracted numerical results indicate that the coupling coefficient depends on the ratio between widths to wavelength. Originality/value: The accurate extraction of the generalised coupling coefficients for graphene surface wave circuits is conducted in this work via an adjustable numerical technique for a novel family of plasmonic couplers. It is derived that only the fundamental propagation features of graphene, such as the wavelength and the confinement of the surface waves, have an effect on the coupling calculation, thus enabling a consistent electromagnetic compatibility study.